2014
DOI: 10.5380/rf.v45i1.34114
|View full text |Cite
|
Sign up to set email alerts
|

WOOD DENSITY OF CLONES OF Eucalyptus urophylla x Eucalyptus grandis IN DIFFERENT CONDITIONS OF GROWTH

Abstract: Variations in the growth site of trees have influence on the internal structure of the trunk. Considering this fact, this study investigated influence of the characteristics of the growth site on wood specific gravity of two clones of Eucalyptus urophyllax Eucalyptus grandis,  approximately six years old, growing in different altitudes and topographies. Furthemore, two methods of sampling of the wood specific gravity were studied, for comparison purpose. Results showed that wood specific gravity underwent vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…In the same way, the higher the percentage of volume occupied by the woody substance, the higher the basic density. Meneses et al (2015) and Mauri et al (2015) in research with the clone GG100, observed basic density variation of 400 kg/m³ to 470 kg/m³ and 460 kg/m³ to 510 kg/m³, respectively. These values are similar with that seen in Table 2 for the same clone.…”
Section: Initial Moisture Content and Basic Densitymentioning
confidence: 97%
“…In the same way, the higher the percentage of volume occupied by the woody substance, the higher the basic density. Meneses et al (2015) and Mauri et al (2015) in research with the clone GG100, observed basic density variation of 400 kg/m³ to 470 kg/m³ and 460 kg/m³ to 510 kg/m³, respectively. These values are similar with that seen in Table 2 for the same clone.…”
Section: Initial Moisture Content and Basic Densitymentioning
confidence: 97%
“…Considerada um dos parâmetros mais importantes da madeira, por sua facilidade de determinação, a densidade básica é também uma característica usada como critério para a determinação da utilização da madeira e, portanto, um parâmetro de avaliação da qualidade, relacionado aos diversos setores no mercado florestal (Mauri et al, 2015). Junto a outras características da madeira, como fuste de boa qualidade, maior volume e rápido crescimento, a densidade é um fator muito importante para a escolha das espécies selecionadas e destinadas aos programas de melhoramento para a indústria de celulose (Eleotério et al, 2015).…”
Section: Introductionunclassified
“…O conhecimento da interação do genótipo com o ambiente permite analisar quais as melhores áreas para o plantio, a produtividade quanto à massa de matéria seca por hectare e, ainda, fornece o suporte à estimativa econômica da floresta (Mauri et al, 2015).…”
Section: Introductionunclassified